Magnetically-responsive hydrogels for modulation of chondrogenic differentiation - Popa, Elena Geta (2016)
Magnetic nanoparticles (MNPs) are attractive tools to overcome limitations of current regenerative medicine strategies, demonstrating potential to integrate therapeutic and diagnostic functionalities in highly controlled systems. In traditional tissue engineering (TE) approaches, the MNPs association with stem cells in a three-dimensional (3D) template offers the possibility to achieve a mechano-magnetic responsive system, enabling remote control actuation. Herein, we propose to study the role of MNPs integrated in Îº-carrageenan (ÎºC) hydrogels in the cellular response of human adipose-derived stem cells (hASCs) aiming at cartilage TE applications. The results indicated that the concentration of MNPs in the ÎºC hydrogels influences cellular behavior, tuning a positive effect on cell viability, cell content and metabolic activity of hASCs, with the most promising outcomes found in 5% MNP-ÎºC matrices. Although hASCs laden in MNPs-free- and MNPs-ÎºC hydrogels showed similar metabolic and proliferation levels, MNPs ÎºC hydrogels under magnetic actuation evidenced an instructive effect on hASCs, at a gene expression level, towards chondrogenic phenotype even in basic medium cultures. Therefore, the MNPs-based systems developed in this study may contribute to advanced strategies towards cartilage-like engineered substitutes.